Analysis of Bee in Quranic Perspective: Surah Al-Nahl - Aisyah Humairaa Muhammad Faisal,; Maryam Mokhtar,; Tg Ainul Farha Tg Abdul Rahman,; Nurdalila A’wani Abdul Aziz; Faszly Rahim (Universiti Sains Islam Malaysia, 2024)
Junior Researcher International Conference (iJURECON) Kolej Genius Insan (KGI) 17 dan 18 November 2020 Pages : 274-277